Development of a counseling framework for mothers of children with perinatally acquired human immunodeficiency virus disease - Ridulme, Queenie Roxas; Gomez, Marie Grace A.; Muega, Maricris Acido; Bagarinao, Ricardo T.; Javiniar, Joel C.; Agapito, Josephine D. (Quezon City College of Education, University of the Philippines Diliman, 2024)
HIV knowledge and awareness are only now starting to rise in the Philippines. The country has one of the fastest rates of case increase worldwide. This study aimed to develop a counseling framework for mothers of children with PAHD using the grounded theory approach. Specifically, this study aimed to determine the mother’s experiences with the treatment being used to manage their child’s disease and treatment as well as how they manage their own. The study utilized qualitative research with a Straussian grounded-theory design and an active interview approach. Interviews with mothers of children with PAHD and health professionals were conducted in the SAGIP Unit of the Philippine General Hospital (PGH). All the interviews and FGDs conducted were recorded and transcribed; these were encoded and analyzed in NVIVO. There were several concepts and indicators identified and through several processes five themes emerged: Managing own disease, Managing a child’s disease, Stigma, Psychosocial care and support, and HIV Counseling. Core categories emerged: Call for help; Acceptance and Moving on. Based on the results of the interviews of participants, focus group discussion of health professionals, and review of literature and studies, a counseling framework was developed. This can be utilized by counselors, and health professionals involved in the care of mothers of children with PAHD.
Thesis
Includes bibliographical references (139-152 leaves)
Keywords: AIDS (Disease) -- Patients -- Counseling of -- Philippines; Children of AIDS patients -- Care -- Philippines; AIDS (Disease) in children -- Philippines